The Policy of Free Electricity to Agriculture Sector: Implications and Perspectives of the Stakeholders in India. (July 2021) - Fosli, Jin Kathrine; Reddy, A. Amarender; Rani, Radhika
The Indian central government is pursuing state governments to replace free power supply to agriculture with the Direct Benefit Transfer (DBT). This article examined the free power policy from the perspective of various stakeholders and suggested alternate policies based on a field survey in the state of united Andhra Pradesh (AP), India, in the year 2018. The team interviewed all stakeholders: farmers, economists, policy experts, power distribution companies and administrators. The study team also visited four villages in AP and conducted focus group discussions with farmers to record their perceptions and alternative policy choices. The opinions are substantiated and cross-checked with the published sources. Free electricity for agriculture is seen as a lifeline in drought-prone areas as it helped them to expand the area under irrigation and increase incomes. However, many experienced huge capital expenditures in drilling-failed borewells. Other stakeholders opine that free power leads to overexploitation of groundwater, lowering groundwater levels, rising cost of drilling deep and piling up of power subsidies, and expanding water-guzzling crops like paddy even in water scarce areas, failure of borewells leading to farmer's distress. The study suggests that replacing free power with DBT to farmers will help them maintain their incomes without overexploiting water resources.